2014
DOI: 10.1186/1472-6963-14-211
|View full text |Cite
|
Sign up to set email alerts
|

The Survivor Unmet Needs Survey (SUNS) for haematological cancer survivors: a cross-sectional study assessing the relevance and psychometric properties

Abstract: BackgroundRelevant and psychometrically sound needs assessment tools are necessary for accurate assessment of haematological cancer survivors unmet needs. No previous study has developed nor psychometrically evaluated a comprehensive needs assessment tool for use with population-based samples of haematological cancer survivors. This study aimed to assess the validity and reliability of the Survivor Unmet Needs Survey (SUNS) with haematological cancer survivors.MethodsThe relevance, content and face validity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 52 publications
(100 reference statements)
1
17
0
Order By: Relevance
“…Second, some participants (about 1/3), were > 5 years out from their thyroid cancer treatment and thus their recollection of met needs and (13,14). These would further focus and refine the gaps identified in the current study as well as construct a TC-specific questionnaire for unmet needs similar to what has been done for other cancers or age groups (15,16). Afterwards, interventions to address these gaps, with a particular emphasis on ways to tailor information to specific demographic groups, need to be designed and implemented followed by qualitatively and quantitatively assessing their impact.…”
Section: Discussionmentioning
confidence: 88%
“…Second, some participants (about 1/3), were > 5 years out from their thyroid cancer treatment and thus their recollection of met needs and (13,14). These would further focus and refine the gaps identified in the current study as well as construct a TC-specific questionnaire for unmet needs similar to what has been done for other cancers or age groups (15,16). Afterwards, interventions to address these gaps, with a particular emphasis on ways to tailor information to specific demographic groups, need to be designed and implemented followed by qualitatively and quantitatively assessing their impact.…”
Section: Discussionmentioning
confidence: 88%
“…Five needs assessment tools were identified as having been used with cancer survivors in the post‐treatment setting. These included the Survivor Unmet Needs Survey (SUNS) (Campbell et al., ; Hall, D'Este, Tzelepis, Sanson‐Fisher, & Lynagh, ), the Short Form Survivor Unmet Needs Survey (SF‐SUNS) (Campbell et al., ), Cancer Survivors Unmet Needs (CaSUN) (Hodgkinson et al., ), Cancer Needs Questionnaire Young People (CNQ‐YP) (Clinton‐McHarg, Carey, Sanson‐Fisher, D'Este, & Shakeshaft, ) and the Childhood Cancer Survivors Study Needs Assessment Questionnaire (CCSS‐NAQ) (Cox et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table , the development and validation of the needs assessment tools analysed were conducted in cross‐sectional studies. Recruitment of patients to the studies was poor, with participation rates ranging from 37% (Hall et al., ) to 58% (Hodgkinson et al., ). Consequently, these studies run the risk of response bias; the extent of which is difficult to determine as most of the studies did not collect comprehensive demographic data on non‐participants.…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 ] Internal consistency of the SUNS was further tested in two studies of hematological cancer survivor cohorts. A cross-sectional study with 529 hematological cancer survivors[ 18 ] demonstrated overall Cronbach's alpha values >0.9, and a weighted Kappa coefficient score of >0.6 for test–retest reliability; acceptability was reported for 40/89 (45%) items. Qualitative data from 17 semi-structured interviews indicated that the SUNS was considered relevant by this cohort of hematological cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative data from 17 semi-structured interviews indicated that the SUNS was considered relevant by this cohort of hematological cancer survivors. [ 18 ] A cross-sectional study of hematological cancer survivors from Australia and Canada ( n = 437) reported similar levels of unmet needs across the two cohorts using the SUNS, with fatigue ( n = 76, 17%) and financial concerns ( n = 39, 9%) rated as high unmet needs. [ 9 ] Despite the clinical utility of the original SUNS, it was considered potentially burdensome for use in the clinical setting given the large number of items ( n = 89).…”
Section: Introductionmentioning
confidence: 99%